Updated lung cancer staging system. (December 2009) - Rami-Porta, Ramon; Chansky, Kari; Goldstraw, Peter
The tumor, node and metastasis classification of malignant tumors is periodically revised. Its seventh edition includes the updated classification for lung cancer, based on the analyses of the International Association for the Study of Lung Cancer international database. It is the largest validation ever carried out to date: 100, 869 patients registered in 46 databases from 20 countries. The analysis of this database allowed a detailed study of the impact of tumor size on prognosis, the reclassification of additional tumor nodules, the reclassification of pleural dissemination and the separation of two groups of metastatic disease. These changes led to modifications in stage grouping that better differentiate tumors with different prognosis. This updated classification is also recommended for small-cell lung cancer, and for broncho––pulmonary carcinoids. A new international nodal map with stations and zones, and a histological definition of visceral pleura invasion, have also been proposed.